SISTEM PENGAMBILAN KEPUTUSAN KREDIT RUMAH DENGAN METODE FUZZY SIMPLE ADDITIVE WEIGHTING - Marganda Simarmata (Universitas Methodist Indonesia, 2015)
Housing Loan Approval (HLA) by the customer at a bank is often hampered and longer because the approval process is done by hand because it must be done carefully in accordance with specified criteria. The weakness of this manual be reasons for Decision Making System for approving HLA approvals at one bank as a guarantor loan repayment funds. In this research, a system built using Fuzzy Simple Additive Weighting Multiple Attribute Decission Making. The design of this application program created using Visual Studio 6.0 programming language and database design by using Microsoft Accses 2007 and Seagate Crystal Reports 8.5 for report generation or the required output. Results obtained from the system designed can help the head of the bank or management decision makers to decide prospective HLA customers quickly, easily and accurately